DEVELOPMENT OF CROSSWORD LEARNING MEDIA USING ECLIPSE CROSSWORD ON ADDITIVE AND ADDICTIVE SUBSTANCE MATERIAL IN CLASS VIII SMP/MTs - Damayanti, Rina Damayanti; Oktaffi Arinna Manasikana; Dyah Ayu Fajarianingtyas; Tita Tanjung (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2025)
The aim of this research is to describe the process of developing crossword puzzle learning media using the eclipse crossword on additive and addictive substance material for class VIII SMP/MTs students. The media development procedure uses ADDIE which includes the Analyze, Design, Development, Implementation and Evaluation stages. This research also aims to determine the results of the validation of crossword puzzle learning media using the eclipse crossword on additive and addictive substance material for class VIII SMP/MTs students carried out by experts. After going through the validation stage, the final product is then described thoroughly. Obtaining research data using media validation sheets and material validation. The results of the research revealed that crossword puzzle media development using the eclipse crossword on additive and addictive substance material had gone through a validity test and received suggestions and input from three validators, namely two experts and one practitioner consistingof media experts, science material experts, and SMP/MTs science practitioner expert. The results of the assessment by media expert validators obtained an average score of 3.57 in the